Case-control study of overweight, obesity, and colorectal cancer risk, overall and by tumor microsatellite instability status - Campbell, Peter T.; Jacobs, Elizabeth T.; Ulrich, Cornelia; Figueiredo, Jane C.; Poynter, Jenny N.; McLaughlin, John R.; Haile, Robert W.; Jacobs, Eric J.; Newcomb, Polly A.; Potter, John D.; Le Marchand, Loïc; Green, Roger C.; et al. (Journal of the National Cancer Institute, 2010)
Being overweight or obese is an established risk factor for colorectal cancer, more so for men than for women. Approximately 10%-20% of colorectal tumors display microsatellite instability (MSI), defined as the expansion or contraction of small repeated sequences in the DNA of tumor tissue relative to nearby normal tissue. We evaluated associations between overweight or obesity and colorectal cancer risk, overall and by tumor MSI status.The study included 1794 case subjects with incident colorectal cancer who were identified through population-based cancer registries and 2684 of their unaffected sex-matched siblings as control subjects. Recent body mass index (BMI), BMI at age 20 years, and adult weight change were derived from self-reports of height and weight. Tumor MSI status, assessed at as many as 10 markers, was obtained for 69.7% of the case subjects and classified as microsatellite (MS)-stable (0% of markers unstable; n = 913), MSI-low (>0% but <30% of markers unstable; n = 149), or MSI-high (≥30% of markers unstable; n = 188). Multivariable conditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). All statistical tests were two-sided.Recent BMI, modeled in 5 kg/m2 increments, was positively associated with risk of colorectal cancer for men and women combined (OR = 1.24; 95% CI = 1.15 to 1.34), for women only (OR = 1.20; 95% CI = 1.10 to 1.32), and for men only (OR = 1.30; 95% CI = 1.15 to 1.47). There was no interaction with sex (P = .22). Recent BMI, per 5 kg/m2, was positively associated with the risk of MS-stable (OR = 1.38; 95% CI = 1.24 to 1.54) and MSI-low (OR = 1.33; 95% CI = 1.04 to 1.72) colorectal tumors, but not with the risk of MSI-high tumors (OR = 1.05; 95% CI = 0.84 to 1.31).The increased risk of colorectal cancer associated with a high BMI might be largely restricted to tumors that display the more common MS-stable phenotype, suggesting further that colorectal cancer etiology differs by tumor MSI status.
Gesehen am 29.03.2023